2020
DOI: 10.1021/acs.energyfuels.0c02384
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Al-Doped Ni–Mn–O Catalysts for Auto-Thermal Reforming of Acetic Acid: Role of MnAl2O4 for Stability of Ni Species

Abstract: Auto-thermal reforming (ATR) of acetic acid (HAc) from renewable bio-oil is an alternative route for hydrogen production, and a series of Ni/Mn­(II)­Al­(III)­O x±δ catalysts were prepared via co-precipitation method and tested in the ATR of HAc. Different parameters including reaction temperatures, O/C molar ratios, gas-hourly space velocity (GHSV), and stability were investigated. The optimal Ni0.39Mn1.61AlO4.31±δ catalyst exhibited excellent catalytic performance in a 50 h ATR test: HAc was converted to H2-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been reported that manganese oxides exhibit multivalent properties, including Mn 2+ , Mn 3+ and Mn 4+ ionic states [ 19 , 20 ]. The redox reactions occurring between these multivalent states can generate surface oxygen species and lattice oxygen vacancies, which in turn enhances the mobility of oxygen species and facilitates gasification of carbon precursors (C*) [ 21 , 22 , 23 , 24 , 25 ]. For example, Deng et al reported that the incorporation of Ag through a hydrothermal method promoted the formation of oxygen defects within the MnO x matrix, while the abundant reactive oxygen species facilitated the combustion of volatile organic compounds (VOCs) and the elimination of O 3 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that manganese oxides exhibit multivalent properties, including Mn 2+ , Mn 3+ and Mn 4+ ionic states [ 19 , 20 ]. The redox reactions occurring between these multivalent states can generate surface oxygen species and lattice oxygen vacancies, which in turn enhances the mobility of oxygen species and facilitates gasification of carbon precursors (C*) [ 21 , 22 , 23 , 24 , 25 ]. For example, Deng et al reported that the incorporation of Ag through a hydrothermal method promoted the formation of oxygen defects within the MnO x matrix, while the abundant reactive oxygen species facilitated the combustion of volatile organic compounds (VOCs) and the elimination of O 3 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research group of Huang, Wang, Xie and co-workers has been prolific in recent years in successfully investigating Ni, Co, Ni-Mn, Ni-Co based catalysts for ATR of HAc on various novel supports such as perovskites and double layered hydroxides at laboratory scale [10][11][12][13][14][15][16][17]. Steady conversion efficiencies (2.7-3 mol H 2 /mol HAc.)…”
Section: Introductionmentioning
confidence: 99%